COMPARATIVE ADVANTAGE AND EXPORT TRADE SPECIALIZATION OF INDONESIA'S NON-CITRUS ESSENTIAL OILS IN THE GLOBAL MARKET, 2015–2024 - Novita Ramadhianti; Suhaeni; Indrajit Wicaksana (RADJA PUBLIKA, 2026)
Non-citrus essential oils are natural resource–based export commodities with significant potential in international trade. Competition with major exporting countries and the dynamic development of the global market share require a comprehensive analysis of Indonesia's export position and competitiveness. This study aims to analyze the comparative advantage, trade specialization, and dynamic export position of Indonesia's non-citrus essential oils relative to competing countries during the 2015–2024 period. The analytical methods employed include the Revealed Comparative Advantage (RCA), Trade Specialization Index (ISP), and Export Product Dynamics (EPD). Secondary data were obtained from UN Comtrade, ITC Trade Map, and Statistics Indonesia. The results show that Indonesia possesses a strong comparative advantage, as indicated by an increase in the RCA value from 3.45 in 2015 to 7.57 in 2024, accompanied by a rise in export market share from 3.16% to 8.38%. The ISP analysis yields an average value of 0.14, with an increasing trend from −0.19 in 2016 to 0.57 in 2024, indicating a shift in Indonesia's status from a net importer to a net exporter. Furthermore, the EPD analysis places Indonesia in the Rising Star position with X-axis = 17.96 and Y-axis = 2.927, indicating that Indonesia's export market share growth aligns with increasing global demand. These findings confirm Indonesia's substantial potential to strengthen its position as a major exporter of non-citrus essential oils in the international market.